Cơ sở khoa học và giải pháp phát triển du lịch bền vững ở Việt Nam - Phạm, Trung Lương (2011)
Tác giả: Phạm Trung Lương, PGS,TS; Hoàng Hoa Quân; Nguyễn Văn Thanh; Nguyễn Văn Lưu -- Từ khóa: Phát triển; Du lịch; Bền vững; Việt Nam